2018
DOI: 10.1130/g45663.1
|View full text |Cite
|
Sign up to set email alerts
|

Death near the shoreline, not life on land: Ordovician arthropod trackways in the Borrowdale Volcanic Group, UK

Abstract: The Borrowdale Volcanic Group of northern England hosts Late Ordovician arthropod trackways that are frequently cited as the earliest unequivocal evidence for animal life on land, and provides a key geological locality for our understanding of global myriapod evolution and terrestrialization. Original fieldwork at the trace fossil site has identified four additional bedding surfaces that yield 121 new trackways at the site (of a total 158 known individuals), and permit better sedimentological and paleoecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…These arthropod trackways were formerly regarded as subaerial in origin (38), and the gait of the tracemaker is compatible with locomotion by penicillate millipedes (39). However, sedimentary structures in the trace-bearing strata indicate locomotion on ash deposited subaqueously (40), thereby weakening the case for a crown group millipede as the tracemaker. The inferred pre-Silurian history of the myriapod crown group has been recognized as an example of a general bias in the terrestrial fossil and rock records.…”
Section: Discussionmentioning
confidence: 99%
“…These arthropod trackways were formerly regarded as subaerial in origin (38), and the gait of the tracemaker is compatible with locomotion by penicillate millipedes (39). However, sedimentary structures in the trace-bearing strata indicate locomotion on ash deposited subaqueously (40), thereby weakening the case for a crown group millipede as the tracemaker. The inferred pre-Silurian history of the myriapod crown group has been recognized as an example of a general bias in the terrestrial fossil and rock records.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Briggs et al (2019) for their Comment on our recent paper (Shillito and Davies, 2019). Our work reported a number of arthropod trackways from the Ordovician Borrowdale Volcanic Group (BVG), demonstrated that the trace fossils were hosted within very fine dacitic tuffs, and, coupling this with trackway morphology, proposed that the tracemakers had been lethally stressed by the presence of volcanic ash.…”
mentioning
confidence: 83%
“…Our paper shows that the only sedimentological evidence at the BVG locality is for subaqueous deposition and, potentially, emergent substrates: not freshwater lacustrine conditions. Briggs et al contend that a lacustrine environment 'remains likely' because other parts of the 6-km-thick BVG appear to be non-marine in origin (but see the discussion in Shillito and Davies [2019]). They imply that the global singularity of a trace fossilbearing Ordovician lacustrine succession is not suspect because (1) there is a rarity of non-marine strata of this age globally.…”
mentioning
confidence: 99%
“…Perhaps more familiarly, walking tracks (repichnia) of arthropods have an extensive geological history, spanning from the Cambrian (and possibly latest Precambrian ( Chen et al, 2018 )) through the Holocene ( Eiseman & Charney, 2010 ). They constitute some of the earliest evidence of metazoan life venturing onto land (reviewed in Minter et al (2016a , 2016b) ) and are known from virtually every paleoenvironment, from near shore and shallow marine environments ( Collette, Hagadorn & Lacelle, 2010 ; MacNaughton et al, 2002 ; Pirrie, Feldmann & Buatois, 2004 ; Shillito & Davies, 2018 ; Trewin & McNamara, 1994 ) and, terrestrially, from proglacial systems ( Anderson, 1981 ; Lima, Minter & Netto, 2017 ; Lima et al, 2015 ; Uchman, Kazakauskas & Gaigalas, 2009 ; Walter, 1985 ) to desert ergs ( Gilmore, 1927 ; Good & Ekdale, 2014 ; Sadler, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kouphichnium , are also present. Ichnospecies of Bifurculapes have been variably attributed to insects, possibly beetles, and to crustaceans ( Getty, 2016 , 2018 ; Hitchcock, 1858 , 1865 ); ichnospecies of Diplichnites have been attributed to myriapods ( Briggs, Rolfe & Brannan, 1979 ; Davis, Minter & Braddy, 2007 ; Pollard, Selden & Watts, 2008 ; Shillito & Davies, 2018 ), notostracans ( Lucas et al, 2006a ; Minter et al, 2007 ), and other arthropods ( Melchor & Cardonatto, 2014 ; Minter et al, 2007 ); and ichnospecies of Kouphichnium have been attributed to limulids ( Caster, 1944 ; King, Stimson & Lucas, 2019 ; Lomax & Racay, 2012 ).…”
Section: Introductionmentioning
confidence: 99%